2012
DOI: 10.1021/nl300351j
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Properties of Gold Nanoparticles Separated from a Gold Mirror by an Ultrathin Oxide

Abstract: That a nanoparticle (NP) (for example of gold) residing above a gold mirror is almost as effective a surface enhanced Raman scattering (SERS) substrate (when illuminated with light of the correct polarization and wavelength) as two closely coupled gold nanoparticles has been known for some time. The NP-overmirror (NPOM) configuration has the valuable advantage that it is amenable to top-down fabrication. We have fabricated a series of Au-NPOM substrates with varying but thin atomic layer-deposited oxide spacer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
276
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 268 publications
(285 citation statements)
references
References 49 publications
7
276
2
Order By: Relevance
“…A nanoparticle-on-mirror (NPoM) [35,36] configuration is adopted [ Fig. 1(c), inset] to provide robust reproducible plasmon enhancements on self-assembled molecular monolayers (SAMs) sandwiched inside the gap.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
“…A nanoparticle-on-mirror (NPoM) [35,36] configuration is adopted [ Fig. 1(c), inset] to provide robust reproducible plasmon enhancements on self-assembled molecular monolayers (SAMs) sandwiched inside the gap.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
“…Usually, Au NPs aggregates or dimmers are known to be excellent SERS substrates. Recently, Moskovits and coworkers evidenced the NP-overmirror (NPOM) -that is to say NPs on top of au film coated with a thin dielectric layer -allows SERS signal enhancement by a factor 10 even for aggregates [59]. Wang et al, confirmed these results by focusing -both numerically and experimentally -on SERS gap modes when molecules are located in-between au NP dimmers and Au film [60].…”
Section: Towards Plasmonic Waveguides For Biosensingmentioning
confidence: 93%
“…This can be understood in terms of the electromagnetic "hot sites" formed at the gaps between two Au nanoparticles. 20,21 The Raman signal did not increase further, however, even after the adsorption of additional 1,4-PDI onto the vacant surfaces of the second group of Au nanoparticles. This is consistent with the observation of Chumanov et al that the additional exposure of the NAMF substrates to the same molecules did not yield more SERS signal, suggesting that the size of hot site is in fact very limited.…”
Section: 16mentioning
confidence: 91%